2020
DOI: 10.3389/fvets.2020.00516
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to the Poultry Industry: Current Perspectives and Strategic Future After the COVID-19 Outbreak

Abstract: Poultry immunity, health, and production are several factors that challenge the future growth of the poultry industry. Consumer confidence, product quality and safety, types of products, and the emergence and re-emergence of diseases will continue to be major challenges to the current situation and the strategic future of the industry. Foodborne and zoonotic diseases are strictly linked with poultry. Eradication, elimination, and/or control of foodborne and zoonotic pathogens present a major challenge to the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
214
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(218 citation statements)
references
References 118 publications
(213 reference statements)
0
214
0
4
Order By: Relevance
“…Other authors have reported similar results, where all ciprofloxacin-resistant Campylobacter strains carried the same mutation (Woźniak-Biel et al, 2018;Elhadidy et al, 2020). Given the long-term use of tetracyclines in feed additives for livestock and poultry, large numbers of tetracycline-resistant isolates are found in animal reservoirs (Premarathne et al, 2017;Hafez and Attia, 2020). It has previously been reported that 95.6% of C. jejuni isolates from chickens, 97.5% of C. coli isolates from chickens and 97.5% of C. coli isolates from pigs in China were resistant to tetracycline (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Other authors have reported similar results, where all ciprofloxacin-resistant Campylobacter strains carried the same mutation (Woźniak-Biel et al, 2018;Elhadidy et al, 2020). Given the long-term use of tetracyclines in feed additives for livestock and poultry, large numbers of tetracycline-resistant isolates are found in animal reservoirs (Premarathne et al, 2017;Hafez and Attia, 2020). It has previously been reported that 95.6% of C. jejuni isolates from chickens, 97.5% of C. coli isolates from chickens and 97.5% of C. coli isolates from pigs in China were resistant to tetracycline (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 59%
“…With this increase in fluoroquinolone-resistant Campylobacter, macrolides have become common drugs in treatment of campylobacteriosis (Luangtongkum et al, 2009). Macrolides, including tylosin, tilmicosin, tulathromycin, and tildipirosin, have been widely used in animal production in many countries (Poehlsgaard et al, 2012;McEwen and Collignon, 2018), and macrolide-resistant Campylobacter strains have been isolated in many regions (Kaakoush et al, 2015;Zhang et al, 2016) and from animals (Wang et al, 2016;Lim et al, 2017;Hafez and Attia, 2020). Tetracycline has also been extremely widely used in animal farming because it has broad-spectrum antibacterial activity, low cost, and excellent efficacy (Chopra and Roberts, 2001), and it may have cause high tetracycline resistance in Campylobacter from food-producing animals (Premarathne et al, 2017;Woźniak-Biel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are no reported cases of the corona virus transfer to chickens, optimizing the immune status of the birds in the farm is also a major priority to keep the health of the flocks at optimum to face any other outbreaks and infectious agents. This includes execution of a strict health program to avoid occurrence of viruses such as avian influenza or any other respiratory avian diseases (15,16). The elements of a good health program are good vaccination, disinfecting, cleaning, continuous monitoring, and pest control (1).…”
Section: Key Challenges To the Local Poultry Industry During The Covimentioning
confidence: 99%
“…Group 3 of CoVs contains viruses that infect a wide range of fowl species (37). IBV is a contagious virus causing high economic losses to the poultry industry (42). It spreads by aerosols because of its replication in the upper respiratory tract and the epithelial surfaces of the alimentary canal, as well as kidneys, gonads, and bursa, causing a dramatic drop in egg production (26,37).…”
Section: Bird Covsmentioning
confidence: 99%